2016 88th ARFTG Microwave Measurement Conference (ARFTG) 2016
DOI: 10.1109/arftg.2016.7839731
|View full text |Cite
|
Sign up to set email alerts
|

CAD-assisted microwave characterization of ink-jet printed CPW on PET substrates

Abstract: Abstract-This paper describes the computer-aided-design (CAD)-assited microwave characterization of coplanar waveguide (CPW) lines formed by ink-jet printed technology on flexible polyethylene terephthalate (PET) substrates. A spacemapping technique is used to link the measured results with simulations and the mapping is used to extract the electrical properties of the ink and supporting dielectric spacer employed during measurements. Results indicate that the losses in lines are predominantly due to the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Our approach enabled repeatable measurements for inkjet printed CPWs on a flexible PET substrate from 10 MHz to 20 GHz. In addition, we showed that with electromag-netic simulation and optimization, it is possible to characterize the ink and supporting materials [26]. This paper develops and expands the main aspects of our previous work, and includes the following new significant additions: 1) A robust technique that reduces the computing resources and is able to obtain the values of the ink conductivity and spacer dielectric constant, 2) The technique automates all the subtasks involved in CAD modeling and optimization, thereby facilitating an efficient and concurrent parameter extraction framework, 3) Demonstration of the sensitivity of the CAD-assisted method to changes in fabrication, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach enabled repeatable measurements for inkjet printed CPWs on a flexible PET substrate from 10 MHz to 20 GHz. In addition, we showed that with electromag-netic simulation and optimization, it is possible to characterize the ink and supporting materials [26]. This paper develops and expands the main aspects of our previous work, and includes the following new significant additions: 1) A robust technique that reduces the computing resources and is able to obtain the values of the ink conductivity and spacer dielectric constant, 2) The technique automates all the subtasks involved in CAD modeling and optimization, thereby facilitating an efficient and concurrent parameter extraction framework, 3) Demonstration of the sensitivity of the CAD-assisted method to changes in fabrication, e.g.…”
Section: Introductionmentioning
confidence: 99%